ARANSEMEN LAGU MAU DIBAWA KEMANA UNTUK ENSEMBEL MUSIK SEKOLAH - Aditya Mahendra; Wimbrayardi Wimbrayardi; Esy Maestro (FBS Universitas Negeri Padang, 2013)
Abstract The arrangement of Mau Dibawa Kemana for the school in music ensemble was inspired based on (1) Mau Dibawa Kemana was one phenomenal Indonesian pop song talked about dilemmatic relationship between two lovers (2) the intention to have the students to be able to play its arrangement in the form of school music ensemble (3) the arrangement which was played by using western music instruments provided t school Kata kunci: Aransemen, Lagu Mau Dibawa kemana, Ensembel, Musik Sekolah.